Conceptions of Accounting and Expectations of Learning Accounting - Teixeira, Cláudia; Gomes, Delfina; Borges, Janete (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2016)
The current study reports on the results of research into introductory accounting students’ conceptions of accounting and expectations of learning the subject of accounting within Portuguese higher education. The results validate the use of the ELAcc inventory in Portuguese higher education and are in line with the literature that argues that subject area has an influence on aspects of learning. In particular, they point out the differences between specialist and non-specialist students’ conceptions of accounting and their expectations of learning accounting. This circumstance highlights the need to consider the different programmes in which introductory accounting is taught.